Effects of particle sizes on total catechin content and antioxidant activity of Musa paradisiaca inflorescence using supercritical carbon dioxide (SFE-CO2)) extraction - Qing, Chong Xiu; Hean, Chong Gun; Nik Hadzir, Noor Hadzuin (SRN Intellectual Resources, 2024)
The inflorescence of Musa paradisiacal or Banana Nipah primarily serves as a staple food crop in Malaysia. It contains various polyphenols, including catching, renowned for its excellent ant oxidative properties. Supercritical carbon dioxide (SFE-CO2) is a green technology that preserves bioactive components while facilitating extraction. This study employed SFE-CO2 to investigate the catching extraction from different size ranges of M. paradisiacal inflorescences at different extraction parameters. The plant matrices (450 - 600 µm, 600 - 850 µm, and 850 µm - 1600μm) were extracted under different temperatures (40°C and 60°C) and pressures (25MPa and 45MPa), with a constant supercritical CO2 fluid and 50% (v/v) ethanol co-solvent flowed at 4 mL/min. Data were analyzed using ANOVA in Minitab Software. The results indicated that the smallest particles (450 - 600 µm) exhibited the highest total oil extraction yield (29.40 ± 7.95%) at 60°C; 45 M Pa, while 850 µm - 1600μm particles had the least (9.54 ± 1.60%) at 40°C; 45MPa. Extraction efficacy of SFE-CO2 at 45MPa; 60°C demonstrated a comparable effect (p > 0.05) to the 10-hour Sox let extraction. Smaller plant matrices exhibited higher catching content at 40°C and 45 M Pa, particularly 81.51 ± 1.11 mg (450 - 600 µm). Increased total catching content correlated with higher DPPH radical scavenging activity. Kinetic modeling revealed that 93% to 95% of the catching extraction from the plant matrix followed a first-order kinetic model. In conclusion, the smallest plant matrix (450 - 600 µm) exhibited the highest catching yield and ant oxidative activity when extracted at 45MPa and 40°C.